Podcasts Potention as a Medium for Educating Young People About Mental Health: A Scoping Review - Rery Arfianto; Galuh Mega Kurnia; Muthmainnah (Universitas Airlangga, 2025)
Background: Podcasts a relatively new form of digital media, offer a flexible audio format that can be accessed anytime and anywhere. With the increasing use of podcasts among the younger generation, podcasts have the potential to be a medium for mental health education. Objectives: To explore research findings on the potential of podcasts as an educational medium for young people's mental health. Method: This review utilized three databases PubMed, ProQuest, Science Direct and Science Searched using the main keywords ‘’Health Podcasts‘ and Mental’ and help keywords. Articles were full text, English language, restricted to the last five years and country, as well as full text and free access. Discussion: This study reviewed 11 articles out of 5,372 that were screened and analyzed. Podcasts are used as a reference for mental health education due to easy accessibility, comprehensive mental health literacy, relatable presenters' life experiences, or discussions featuring professionals. podcasts reduce stigma and increase informal help-seeking, reducing feelings of loneliness. Podcasts with different presenter experiences based on demographic profiles and personal experiences of mental health are significant as psychoeducational tools for personal and/or professional development. However, the accuracy, transparency, and credibility of professional websites are still to be evaluated of podcasts as educational media especially related to mental health issues. Conclusions: This study summarizes the potential of podcasts as a significant educational medium for mental health with its various advantages. Mental health experts are needed to produce quality educational podcast content. This content will fulfill the audience's need for accurate and reliable information about mental health.